Air−Liquid Interface Cultures of the Healthy and Diseased Human Respiratory Tract: Promises, Challenges, and Future Directions. Issue 6 (6th May 2021) - Baldassi, Domizia; Gabold, Bettina; Merkel, Olivia M.
Abstract : Air−liquid interface (ALI) culture models currently represent a valid instrument to recreate the typical aspects of the respiratory tract in vitro in both healthy and diseased state. They can help reducing the number of animal experiments, and hence support the 3R principle. This review discusses ALI cultures and co‐cultures derived from immortalized as well as primary cells, which are used to study the most common disorders of the respiratory tract, in terms of both pathophysiology and drug screening. The article displays ALI models used to simulate inflammatory lung diseases such as chronic obstructive pulmonary disease (COPD), asthma, cystic fibrosis, lung cancer, and viral infections. It also focuses on ALI cultures described in literature studying respiratory viruses such as SARS‐CoV‐2 causing the global Covid‐19 pandemic at the time of writing this review. Additionally, commercially available models of ALI cultures are presented. Ultimately, the aim of this review is to provide a detailed overview of ALI models currently available and to critically discuss them in the context of the most prevalent diseases of the respiratory tract. Abstract : Air−liquid interface cultures are used to accurately mimic the human respiratory tract. Different cell types are combined to create a complex in vitro environment. Furthermore, the interaction with different pathogens such as viruses or bacteria can be simulated. Thereby, they represent a useful tool for drug testing and help reduce animal experimentation.